DYNAMICS OF MATRIX METALLOPROTEINASE CONCENTRATION DURING THE TREATMENT OF CHILDREN WITH DILATED CARDIOMYOPATHY'S EARLY DEBUT - A.S. Gasanov; E.N. Basargina; T.V. Bershova (Union of pediatricians of Russia, 2011)
The article shows the effectiveness of the complex treatment (angiotensin converting enzymes inhibitors, blockers, diuretics and cardiac glycosides) in children with dilated cardiomyopathy with an early debut. The dynamic observation of changes in morphological and functional cardiac parameters was carried out and we studied the content of matrix metalloproteinases in 41 patients on the background of the therapy. The statistically significant positive effect of the combined therapy on the studied parameters after 1-1,5 years of the continuous treatment has been demonstrated.Key words: dilated cardiomyopathy, matrix metalloproteinases, treatment, children.